PELAKSANAAN FUNGSI BADAN PERMUSYAWARATAN DESA (BPD) DI DESA KOTOBARU KECAMATAN SINGINGI HILIR KABUPATEN KUANTAN SINGINGI TAHUN 2006-2012 - Abdurrafi "; Chalid Sahuri (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2016)
This research was carried out, aiming to see the extent to which theimplementation of the Village Consultative Body functions in the village KotobaruSingingi Hilir District of Kuantan Singingi Year 2006-2012.In this study, researchers used a theory that explains Amitai Etzioni is a unitof social organization (or grouping humans) are deliberately shaped and reshapedwith consideration in order to achieve certain goals. This research is descriptive andqualitative data collection techniques with interview, observation and documentationwhich will then be deduced.Based on the results of this study indicate that the Organization VillageConsultative Body (BPD) in the village of the District Kotobaru Singingi HilirRegency Kuantan Singingi not run optimally in carrying out its functions.Keywords: Village Consultative Body Function, Organization